2023
DOI: 10.1001/jamanetworkopen.2023.12718
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Clinicians and Staff at Community-Based Opioid Use Disorder Treatment Settings on Linkages With Emergency Department–Initiated Buprenorphine Programs

Abstract: ImportanceAn increasing number of emergency departments (EDs) are initiating buprenorphine for opioid use disorder (OUD) and linking patients to ongoing community-based treatment, yet community-based clinician and staff perspectives regarding this practice have not been characterized.ObjectiveTo explore perspectives and experiences regarding ED-initiated buprenorphine among community-based clinicians and staff in geographically distinct regions.Design, Setting, and ParticipantsThis qualitative study reports fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“… 9 If the proposed amendments are codified into law, buprenorphine access will decrease, and people living in rural areas and underserved communities will likely bear the burden of this proposed change. The change would magnify the barriers identified in the study by Sue et al, 5 as community treatment centers already face limited treatment capacity and difficulties addressing sociostructural marginalization. 5 …”
mentioning
confidence: 99%
See 3 more Smart Citations
“… 9 If the proposed amendments are codified into law, buprenorphine access will decrease, and people living in rural areas and underserved communities will likely bear the burden of this proposed change. The change would magnify the barriers identified in the study by Sue et al, 5 as community treatment centers already face limited treatment capacity and difficulties addressing sociostructural marginalization. 5 …”
mentioning
confidence: 99%
“…The change would magnify the barriers identified in the study by Sue et al, 5 as community treatment centers already face limited treatment capacity and difficulties addressing sociostructural marginalization. 5 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This finding may also reflect increased trust in the health care system associated with the bridge clinic group, as stigma often prevents patients with OUD from seeking and accessing care. A qualitative study that examined the perspectives of community clinicians and staff toward buprenorphine initiated in the emergency department found that barriers to successful OUD treatment linkage included negative attitudes about MOUD, limited treatment capacity, the reported need for specialized addiction clinicians, and addressing the social determinants of health to support treatment engagement . Bridge clinics address many of these while providing stigma-free, low-barrier, and expert addiction care.…”
mentioning
confidence: 99%